Tribal Social Capital in Jordanian Society: A Sociological Study in the Southern Jordan Region - Al-Sarayrah, Ali Jameel; Al Hourani, Mohammed Abdel Karim (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to investigate whether the tribe in Jordanian society serves as social capital for tribal members in the southern region of Jordan. This is achieved by examining components of tribal loyalty and the benefits it provides to individuals. Methods: The study employed a social survey approach, using a multi-stage random sample of 350 males. Males were selected because they are considered the public representatives of the tribe in Jordanian society, including the southern governorates (Karak, Tafila, Ma’an, Aqaba). A questionnaire was used as the primary tool for data collection. Results: The results indicated that the tribe in Jordanian society acts as tribal social capital and that tribal loyalty remains strong. Through this loyalty, individuals gain emotional support, which provides existential security and reassurance, as well as social strength. Tribal loyalty also provides individuals with a homogeneous reference framework. The study found statistically significant differences (at α≤0.05) in tribal loyalty based on place of residence, with higher loyalty observed among village residents compared to city residents. Tribal loyalty continues to represent social capital, particularly in rural areas. Conclusion: Individuals in southern Jordan perceive the tribe as a source of social capital, offering emotional support, solidarity, networking, and access to scarce resources. Despite institutional, legal, and legislative developments in Jordanian society, these changes have not effectively dismantled the role or essence of the tribe. This has left modernity in Jordanian society largely superficial, with traditional units such as tribes maintaining their dominance over formal institutions.